METHODS OF INTENSIFICATION OF THE OPTIMAL OPTIONS OF INTERNAL NOZZLES OF DRUM DRYERS IN THE PROCESS OF MASS EXCHANGE - A.A. Axunbayev; B.X. Ergashev; B.X. Ergashev (Western European Studies, 2024)
The article provides a method of experimental determination of the optimal shape and amount of material of the nozzle of the drum apparatus intended for drying granular materials. Depending on the physical and geometrical parameters of the material, its quantity and occupied surface are experimentally determined during the rotation of the drying drum
Keywords: drying drum; nozzle; natural slope angle